Facile deposition and plasmonic resonance of Ag–Au nanoparticles in titania thin film1. (27th August 2015) - Mathpal, Mohan Chandra; Kumar, Promod; Tripathi, Anand Kumar; Balasubramaniyan, R.; Singh, Manish Kumar; Chung, Jin Suk; Agarwal, Arvind
<x xml:space="preserve">Abstract</x> A systematic diagram of fast and simple fabrication of Ag–Au nanoparticle based plasmonic thin film by spray coating.